2013
DOI: 10.1007/s10103-013-1481-4
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy effect on the muscular activity of regular physical activity practitioners

Abstract: Clinical investigations have demonstrated the effectiveness of phototherapy on the muscle activity. The aim of this study was to investigate the effect of low-level laser therapy (LLLT) on the tibialis anterior muscle of regular physical activity practitioners by electromyographic, biomechanical, and biochemical (lactate) analysis. Double-blind controlled clinical trials were conducted with 12 healthy females, regular physical activity practitioners, between 18 and 30 years. The LLLT application (780 nm, 30 mW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The authors reported an increased number of repetitions in the LLLT group compared to the placebo, but surface electromyography showed no statistical difference. In a similar study, Dos Santos Maciel, Munoz (level 1b) used a muscular preconditioning protocol with LLLT (780 nm) applied on the tiabialis anterior muscle and investigated fatigue in an isokinetic dynamometer combined with surface electromyography analysis. This double‐blind controlled trial reported an increased torque exerted by the tiabialis anterior muscle after muscular preconditioning, but muscle fatigue analyzed by surface electromyography was not reduced, and lactate levels in blood were not significantly different between groups.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported an increased number of repetitions in the LLLT group compared to the placebo, but surface electromyography showed no statistical difference. In a similar study, Dos Santos Maciel, Munoz (level 1b) used a muscular preconditioning protocol with LLLT (780 nm) applied on the tiabialis anterior muscle and investigated fatigue in an isokinetic dynamometer combined with surface electromyography analysis. This double‐blind controlled trial reported an increased torque exerted by the tiabialis anterior muscle after muscular preconditioning, but muscle fatigue analyzed by surface electromyography was not reduced, and lactate levels in blood were not significantly different between groups.…”
Section: Resultsmentioning
confidence: 99%
“…In physically active young women, treatment with photobiomodulation (780 nm, energy of 23.49 J per muscle) before the induction of a protocol of tibialis anterior muscle fatigue increased muscle torque at the beginning of the exercise, compared to the placebo ( dos Santos Maciel et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects seen in recent studies were obtained with red 8,9 and infrared wavelengths 9-13 generated by both laser [8][9][10][11][12][13][14] and LED [14][15][16][17] devices. Various exercises that represent sport-specific activities have been tested: repeated contractions, 8,10,11,13,15 isometric sustained contraction, 9,16,17 cycling, 14 and running. 12 Only a few investigators have compared PBM with other physical agents 18,19 and addressed the effectiveness of laser versus LEDs.…”
mentioning
confidence: 99%